PREPARAÇÃO DE AMINAS ORTO-NAFTOQUINOIDAIS POR MEIO DA ENERGIA DO ULTRASSOM - COUTO, Aliziane,; DA SILVA, Natan,; SILVA, Carlos,; BRAND, George,; OLIVEIRA, Geane,; VALENÇA, Wagner, (ANAIS DO ENIC, 2025)
.